Safety and tolerability of IRL790 in Parkinson's disease with levodopa-induced dyskinesia—a phase 1b trial. (December 2018) - Svenningsson, Per; Johansson, Anders; Nyholm, Dag; Tsitsi, Panagiota; Hansson, Fredrik; Sonesson, Clas; Tedroff, Joakim
Abstract IRL790 is a novel compound with psychomotor stabilizing properties primarily targeting the dopamine D3 receptor. IRL790 is developed as an experimental treatment for levodopa-induced dyskinesia (LID), impulse control disorder, and psychosis in Parkinson's disease (PD). The primary objective was to investigate the safety and tolerability of IRL790 in PD patients with LID in a randomized controlled trial. PD patients with peak-dose dyskinesia were randomized to placebo or IRL790 treatment (1:3 ratio) for 4 weeks. Study drug was given as an adjunct treatment to the patients' regular stable antiparkinsonian medication. Dosing was individually titrated for 14 days, whereafter dosing was kept stable for an additional 14 days. Fifteen patients were randomized to treatment and 13 patients completed the 4-week treatment. Adverse events were mostly reported during the titration phase of the trial. They were mainly central nervous system related and could be mitigated by dose adjustments. There were no serious adverse events. There were no clinically significant changes in vital signs, electrocardiogram, and laboratory parameters due to the treatment. The average dose in the stable dose phase was 18 mg daily, yielding a 2-h post-dose plasma concentration of average 229 nM on day 28. Assessments for motor function showed a numeric reduction in dyskinesia. It is concluded that IRL790 can be safely administered to patients with advanced PD. The results will be of guidance for the design of phase 2 studies. Clinical trial: New drug counters dyskinesia A compound that blocks the dopamine D3 receptor alleviates the abnormal involuntary movements caused by long-term treatment with levodopa. Nearly 50% of Parkinson's disease (PD) patients treated with levodopa for more than 5 years develop levodopa-induced dyskinesia. Previous studies have shown an increase in the levels of D3 receptor in the dorsal striatum of patients experiencing this motor complication. Svenningsson at the Karolinska Institutet, Sweden, and colleagues examined the safety and tolerability of IRL790 in patients with advanced PD and levodopa-induced dyskinesia. After four weeks, no serious adverse events were observed and dyskinesia was reduced in patients receiving IRL790 along with their regular antiparkinsonian medication. Further trials will help determine the optimal dose of IRL790 and whether it could be used to treat other adverse effects associated with long-term levodopa use such as impulse control disorder.